Re-vitalising Locality in Indigenous Tebango Buddhism: Social and Cultural Capitals for Community Wellbeing - Muchammadun, Muchammadun; Amrulloh, Zaenudin; Aditya, Rahadiyand (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2023)
The number of Sasak followers of the indigenous beliefs on Tebango, North Lombok has shrunk significantly since 1965. The causes are complex yet principally it is external pressure to relinquish these traditions, often derogatorily labelled as ‘syncretistic, that has forced many Sasak to abandon their ancestral beliefs for one of the state-recognised religions. Nevertheless, the recent Constitutional Court Decision 97/2016, followed by the Circular Letter (2018) of the Ministry of Internal Affairs, Republic of Indonesia, prompts a re-examination and Revitalization of identity. The paper examines key aspects of this question relevant to contemporary discussions regarding the Tebango Buddhism beliefs. It explores the etymology of the word ‘syncretism’ and highlights the problematic use of the word in Indonesian Studies as reflecting European Orientalist perceptions of non-European cultures whose value judgements are no longer relevant. This paper argues that the dynamics and changes of Tebango Buddha is actually far more historically recent than often thought. Tebango Buddhism beliefs may be understood as the complex outcome of Lombok’s long and dynamic interaction with the wider pesisir world of the archipelago, notably Java during the time of the wali songo, which cannot be simplistically dismissed as ‘syncretism’. A better understanding of this history may contribute to contemporary religious education and community wellbeing in order that young Indonesian Muslims develop a more nuanced, and less biased, understanding of the extraordinary rich – and diverse – history of religion in Indonesia.